The effect of single versus multiple sets on strength - Kelly, S. B.; Brown, L. E.; Coburn, J. W.; Zinder, S. M.; Gardner, L. M.; Nguyen, D. (The Journal of Strength and Conditioning Research, 2007)
Research has previously been divided on whether performing resistance training with a single set per training session is as effective for increasing strength as training with multiple sets. The purpose of this study was to determine the effect of single sets versus multiple sets on strength. Forty subjects were randomly assigned into 1 of 3 groups: control (C; n = 8), single set (SS; n = 14), or multiple sets (MS; n = 18) to perform 8 maximal knee extensions at 60°/s on a Biodex System 3 isokinetic dynamometer twice a week for 8 weeks. The SS group performed 1 set while the MS group performed 3 sets. All groups were pre-, mid- (4 weeks), and posttested at 60/s. Strength was expressed as peak torque (PT). A 3 x 3 x 2 (time x group x sex) mixed factor repeated measures analysis of variance (ANOVA) revealed no interaction involving sex, but there was an interaction of group by time. The MS group exhibited a significant (p < 0.05) increase in PT (pre = 171.39 +/- 61.98 Nm; mid = 193.08 +/- 66.23 Nm) between the pretest and the midtest while the SS (pre = 163.45 +/- 56.37 Nm; mid = 172.60 +/- 61.78 Nm) and C groups (pre = 135.997 +/- 54.31 Nm; mid = 127.66 +/- 53.12 Nm) did not change. Strength did not change between the midtest and the posttest for any group. It was concluded that performing 3 sets of isokinetic knee extensions was more effective than performing a single set for increasing peak torque. These results seem to indicate that for increasing strength of the quadriceps, performing multiple sets is superior to performing a single set of resistance exercise.